2021
DOI: 10.1177/11206721211010613
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of neovascular age related macular degeneration during COVID-19 pandemic: The short term consequences of unintended lapses

Abstract: Aim: To investigate the short-term effects of COVID-19 pandemic related unintended treatment lapses on neovascular age related macular degeneration (nAMD) patients. Methods: In this prospective cross-sectional study, 140 patients who had at least one anti-vascular endothelial growth factor (VEGF) injection for nAMD within 12 months before COVID-19 pandemic and who had at least 3 months of unintended lapse for control visits during pandemic were recruited and underwent a detailed opthalmological examination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 67%
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 67%
“…Similar 6-month results were extracted from a data registry, which stated that VA remained stable if re-treatment interval was extended by not more than 10–12 weeks [ 12 ]. Another study group associated unintended lapses over 3 months with poor functional and structural outcomes for patients with nAMD, especially in unstable clinical courses [ 13 ]. In our study cohort, four eyes with a long treatment interval before the lockdown did not experience a persistent VA loss due to the extended interval (Table 1 V3 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 27 , 28 , 36 In the end, 14 studies (including 1,931 patients) were included in the quantitative synthesis. 4 , 5 , 8 , 24 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 44 , 45 , 46 The PRISMA diagram detailing the study screening process is shown in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%